Sociodemographic determinants of individual taxpayer compliance behavior - Yenni Mangoting; Dean Charlos Padji Dogi; Samuel Thomas Cornelius (Manajemen dan Bisnis, 2026)
This research seeks to investigate the influence of taxpayer awareness, trust, and satisfaction on tax compliance. It further explores whether sociodemographic factors such as age, gender, income, and educational attainment act as moderating variables that strengthen or weaken the relationships between awareness, trust, satisfaction, and tax compliance. This study adopts a quantitative design using a survey approach. The sample comprises 251 individual taxpayers, and the data were gathered through online questionnaires. The analysis was conducted using SEM-PLS. The findings indicate that taxpayer awareness and satisfaction positively affect tax compliance, whereas trust does not show a statistically significant effect. The moderation analysis indicates that age influences the strength of the relationship between awareness and tax compliance. Education level is also found to affect the relationship between satisfaction and compliance. The subsample analysis further shows that the effects of awareness and satisfaction are more pronounced among younger taxpayers and those with lower educational attainment than among older and more highly educated groups. For tax authorities, these results highlight the importance of considering sociodemographic characteristics when designing compliance policies and strategies.